Increasing MS Glow and MS Glow Men Skincare Purchasing Decisions Through Social Media Interaction - Qhoiru Annisa Mustikasari; Parlagutan Silitonga (PT FORMOSA CENDEKIA GLOBAL, 2023)
Beauty and Health for the upper middle class are primary needs like food and drink. Marketers compete to influence potential buyers of their products. The purpose of this study was to improve purchasing decisions with brand equity and price perceptions through the mediating role of social media interactions on MS Glow skincare products. The population in this study were all MS Glow skincare users, using accidental sampling as a sampling technique, namely 150 respondents. Methods of data collection using questionnaires distributed to respondents. The analysis used is path analysis with the help of SmartPLS 3.3. The results showed that the value of each variable directly or indirectly had a positive and significant effect.